Biogas production potential from a native beverage vinasse of Mexico - Abumalé Cruz-Salomón (Diponegoro University, 2017)
This work presents the results of the physicochemical characterization and evaluates the potential of vinasse (a wastewater obtained from local beverage of Chiapas, Mexico) as nutrient source for biogas production by anaerobic digestion in an Upflow Anaerobic Sludge Blanket (UASB) bioreactor. This wastewater contains high level of organic matter, 120.2 ± 18.4 g O2/L of chemical organic demand (COD), 0.77 biodegradability index (BI), and a ratio 21:1 of C/N. The UASB bioreactor had a working volume of 4 L, at 32 oC, 10 days of hydraulic retention time (HRT). The COD removal was of 91 %, the production of methane was 1860 mL/day and 264.83 mL CH4/gCOD of biochemical methane potential (BMP). As such, the UASB bioreactor fed with vinasse can be sustainable alternative for the bioenergy production from wastewater, shifting the paradigm of wastewater management from ‘treatment and disposal’ to ‘beneficial utilization’ as well as ‘profitable endeavor’.